BOOK REVIEW: Women Founders of Waqf (Vakıf Kuran Kadınlar) - Rahmany, Faizah Aulia (SMART Insight, 2025)
The book Vakıf Kuran Kadınlar (Women Founders of Waqf) is a collection of 14 scientific papers resulting from the 2018